2008
DOI: 10.1016/j.actamat.2008.07.046
|View full text |Cite
|
Sign up to set email alerts
|

Twinned dendrite growth in binary aluminum alloys

Abstract: The formation of twinned dendrites (feathery grains) in binary Al-Zn, Al-Mg, Al-Cu and Al-Ni alloys has been studied in specimens directionally solidified under identical thermal conditions, i.e. G % 100 K cm À1, v % 1 mm s À1, and with slight natural convection in the melt. The influence of the solute element nature and content has been found to be of less importance than previously reported since feathery grains were formed in all four alloys, regardless whether the alloying elements are hexagonal close pack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
53
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 20 publications
3
53
1
Order By: Relevance
“…The first argument of Henry is thus put into question. The third question is also unclear, since the present authors [6] did not find any increase in segregation near the twin plane in Al-30 wt.% Zn twinned dendrites. However, this was done on a transverse section of an specimen using wavelength-dispersive X-ray spectroscopy (WDS) chemical analysis in a scanning electron microscope, and not by HRTEM, and thus the resolution was possibly insufficient.…”
Section: Introductionmentioning
confidence: 44%
See 2 more Smart Citations
“…The first argument of Henry is thus put into question. The third question is also unclear, since the present authors [6] did not find any increase in segregation near the twin plane in Al-30 wt.% Zn twinned dendrites. However, this was done on a transverse section of an specimen using wavelength-dispersive X-ray spectroscopy (WDS) chemical analysis in a scanning electron microscope, and not by HRTEM, and thus the resolution was possibly insufficient.…”
Section: Introductionmentioning
confidence: 44%
“…This might explain why Henry observed in these alloys cells in sections nearly parallel to the twin plane and dendrites perpendicular to it, with the consequence that k // ( k \ . In previous works, Salgado-Ordorica and Rappaz [6,7] showed that, in binary Al alloys with relatively high solute-content, k // is comparable to k \ , even though dendrites trunks were aligned along the twin planes. The first argument of Henry is thus put into question.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known in industry that some aluminum alloys are more prone to feathery grains formation than others, but the role of the nature and amount of alloying elements is still not understood. For example, Salgado-Ordorica and Rappaz [7] could produce twinned dendrites in different binary Al alloys with solute elements having a low/high stacking fault energy (Cu and Ni, respectively) or solidifying with a hexagonal close packed structure (Mg and Zn), providing the other conditions were met. Surprisingly, these authors could not produce twinned dendrites in AlZn for compositions higher than 40 wt.%, for which "regular" dendrites (i.e., untwinned) are known to grow not along h1 0 0i directions, as do most cubic-symmetry metals, but along directions which are closer to h1 1 0i [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, the formation of twinned dendrites was shown to occur under specific solidification conditions which can be summarized as follows [6][7][8][9]: (i) poor or no inoculation of the alloy (in order to prevent the formation of equiaxed grains); (ii) high thermal gradient (typically 100 K cm -1 ) and cooling rate (typically 10 K s -1 ) (i.e., growth rate of typically 1 mm s -1 ); (iii) strong convection of hot liquid (e.g. associated with pouring) insofar as it promotes high gradient at the front, as convection induced by stirring drastically decreases the thermal gradient in the liquid and does not promote the formation of twinned dendrites.…”
Section: Introductionmentioning
confidence: 99%